Grand Design for Provincial Expansion in Papua from the Perspective of 7 (Seven) Cultural Regions - Esau Hombore; Khasa Efendy; Sampara Lukman; Kusworo (International Journal of Science and Society, 2023)
This research aims to identify seven cultural regions that can contribute to the development of contemporary and future Papua, while adhering to the principles of the Unitary State of the Republic of Indonesia. This study combines the theory of "Bhinneka Tunggal Ika" and the concept of a cultural approach, with a focus on the threefold spirit of Melanesian brotherhood among the people of Papua. The integration of these two conceptual frameworks is crucial in preserving the nation's existence amidst its diverse population. The goal of this effort is to ensure answers and provide recommendations for a comprehensive development plan for the expansion of the Papua Province. The research prioritizes the use of qualitative data through interviews with informants and respondents. The aim is to explore the potential consequences of regional expansion when approached through a comprehensive cultural lens, based on anthropological and sociological perspectives influenced by Papuan and Melanesian studies. This research is based on the theoretical framework of "Structuralist Anthropology" developed by the Leiden School of Anthropology, with a specific focus on the concept of regionalism known as FoS (Field of Anthropological). The findings of this research examine a comprehensive plan to expand to seven provinces in Papua. From a cultural perspective, this approach is considered a more appropriate solution for realizing a prosperous future for Papua, with the ultimate goal of improving the well-being of its population within the framework of the Unitary State of the Republic of Indonesia.